PENINGKATAN MUTU PEMELIHARAAN MESIN PENGARUHNYA TERHADAP PROSES PRODUKSI PADA PT. ANEKA BUMI PRATAMA (ABP) DI KABUPATEN BATANGHARI - Jasasila Jasasila (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Maintenance or maintenance is an activity to maintain the machine or other production equipment by repairing or replacing the necessary equipment to the existence of the machine satisfactory as expected, while according to Arikunto (2008) Maintenance is a function within a factory company that is as important as the function- Other functions such as production, the purpose of this study is to determine the maintenance of the machine, to know the production process and to determine the effect of machine maintenance on the production process at PT. ABP (Aneka Bumi Pratama) in Kabupaten Batanghari. The method used by distributing the quisioner to the youth respondents was analyzed by using simple linear regression to see the effect of machine maintenance on the production process. Results from the data analysis found that machine maintenance is very influential on the production process.Keyword : Maintance, Machine, Process, Product